A new species of Hypoaspis Canestrini from Iran (Acari: Laelapidae), with a key to the species occurring in the Western Palaearctic Region - Joharchi, Omid; Ostovan, Hadi; Babaeian, Esmaeil (Zootaxa, 2014)
Hypoaspis elegans sp. nov. was collected on adult female Oryctes elegans Prell. (Coleoptera: Scarabaeidae) in Bam, Kerman province, Iran. The new species is described and illustrated from adult females. Hypoaspis surii Khanjani et. al., 2013 is a junior synonym of Hypoaspis maryamae Joharchi & Halliday, 2011. A key to the Western Palaearctic species of Hypoaspis is presented.